FORMULASI HAND AND BODY LOTION BERBASIS EKSTRAK JAMUR LINGZHI (GANODERMA LUCIDUM) SEBAGAI SEDIAAN FOTOPROTEKTIF - Hidayat, Fahmi; Rosanti, Aulia Dewi; Sa’diyah, Asvikatu (Jurnal Buana Farma, 2024)
Ultraviolet (UV) radiation can induce various health problems, particularly on the skin as the body's protective organ. This study aimed to enhance skin protection against free radical damage by utilizing the antioxidant potential of lingzhi mushroom (Ganoderma lucidum) extract. Through the formulation of hand and body lotion, various concentrations of lingzhi mushroom extract (0%, 0.25%, 0.50%, and 0.75%) were incorporated. In vitro testing was conducted to measure the Sun Protection Factor (SPF) value as an indicator of the product's ability to protect the skin from ultraviolet radiation. The results showed an increase in SPF value with increasing concentrations of lingzhi mushroom extract. The formulation with 0.75% lingzhi mushroom extract yielded the highest SPF value of 4.4. These findings indicate that lingzhi mushroom extract has the potential to be an active ingredient in skincare products, not only providing hydration but also offering optimal protection against free radical damage and UV radiation.